2010
DOI: 10.1007/s10329-009-0186-6
|View full text |Cite
|
Sign up to set email alerts
|

Modelling ranging behaviour of female orang-utans: a case study in Tuanan, Central Kalimantan, Indonesia

Abstract: Abstract:Quantification of the spatial needs of individuals and populations is vitally important for management and conservation. Geographic Information Systems (GIS) have recently become important analysis tools in wildlife biology, improving our ability to understand animal movement patterns, especially where very large data sets are collected. This study aims at combining the field of GIS with primatology to model and analyse spaceuse patterns of wild orang-utans. Home ranges of female orang-utans in the Tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 44 publications
0
32
0
Order By: Relevance
“…As data for 1994 were already collected at less frequent intervals, data from this period were not resampled. Because we had already reduced our sample sizes to standardize the number of samples per day across years, we did not further reduce our sample sizes to avoid autocorrelation; however, while some studies consider this to be necessary to properly calculate ranging behavior [Clifford et al, 1989;Hurlbert, 1984;Legendre, 1993;Swihart & Slade, 1985], recent studies have questioned the effectiveness of this process, even with very large datasets [Wartmann et al, 2010], and have also highlighted the potential risk of losing biologically significant information [Asensio et al, 2014;De Solla et al, 1999].…”
Section: Data Collectionmentioning
confidence: 98%
“…As data for 1994 were already collected at less frequent intervals, data from this period were not resampled. Because we had already reduced our sample sizes to standardize the number of samples per day across years, we did not further reduce our sample sizes to avoid autocorrelation; however, while some studies consider this to be necessary to properly calculate ranging behavior [Clifford et al, 1989;Hurlbert, 1984;Legendre, 1993;Swihart & Slade, 1985], recent studies have questioned the effectiveness of this process, even with very large datasets [Wartmann et al, 2010], and have also highlighted the potential risk of losing biologically significant information [Asensio et al, 2014;De Solla et al, 1999].…”
Section: Data Collectionmentioning
confidence: 98%
“…We chose an 80% home range because it was the largest area that was not influenced by group locations associated with nonforaging events, e.g., predispersing juvenile exploring the area, intergroup encounters. Computation of the Swihart and Slade and the Schoener indices to assess the autocorrelation of data points (Swihart and Slade 1985;Wartmann et al 2010) indicated that the data used for the home range estimates of E350 did not autocorrelate; the data of CC and D500 showed some acceptable levels of autocorrelation (S&S: 0.67 and 0.66, Schoener's: 1.55 and 1.37), whereas the E500 data autocorrelate only according to the Schoener index (1.58).…”
Section: Home Ranges and Demographymentioning
confidence: 99%
“…To obtain 50% and 80% probability areas we used the fixed Kernel density estimator with an automated smoothing parameter (h=0.346) with biased-cross validation in ArcGIS 9.1 (Wartmann et al 2010). The 50% area identifies a core area that was used intensively and almost exclusively (Fig.…”
Section: Home Ranges and Demographymentioning
confidence: 99%
“…Orangutans may simply capture slow lorises during food scarcity because they spend more time traveling in search of food, and thus are more likely to encounter a slow loris by chance. This, however, is unlikely, because orangutans reduce travel and feeding time and increase resting time during food scarcity (Knott 1998; Wartmann et al 2010). Moreover, other differences in range may not be sufficient to explain the occurrence of slow loris hunting because males have wider ranges than females (Singleton and van Schaik 2001), but slow loris hunting is not biased toward males (van Schaik et al 2009), and because not all females of the same population, which experience the same periods of food scarcity, show this behavior.…”
Section: Discussionmentioning
confidence: 99%